FDA and intellectual property strategies for medical device technologies. (2019) - Jr, Halt, Gerald B; Jr, Donch, John C; Stiles, Amber R; VanLuvanee, Lisa Jenkins; Theiss, Brandon R; Blue, Dana L
No abstract available